Cotard Delusion in the Context of Schizophrenia: A Case Report and Review of the Literature - Bott, Nicholas; Keller, Corey; Kuppuswamy, Malathy; Spelber, David; Zeier, Joshua (Frontiers in Psychology, 2016)
Background: The Cotard delusion (CD) is one of a variety of narrowly defined monothematic delusions characterized by nihilistic beliefs about the body’s existence or life itself. The presence of CD within the context of schizophrenia is rare (<1%), and remains understudied. Case: ‘Mr. C’ is a 58-year-old veteran with a prior diagnosis of schizophrenia, who presented with CD in the context of significant depression, suicidal ideation, violence, and self-harm behavior. He perseverated in his belief that he was physically dead and possessed by demons for several weeks. This delusion was reinforced by his religious belief that life was an attribute of God, and by inference, he as a human, was dead. His condition gradually improved over the course of treatment with Divalproex and quetiapine with discussions about the rationale for his belief. Upon discharge, Mr. C. demonstrated awareness of his fixation on death and an ability to redirect himself. Discussion: This case highlights the need to better understand the co-occurrence of CD in schizophrenia, their differentiation, the increased risk of violence and self-harm behavior in this presentation, and how specific events and religious factors can influence delusional themes of CD. Pharmacotherapy and aspects of cognitive-behavioral therapy may be effective in ameliorating these symptoms in CD.